CLINICAL AND LABORATORY FEATURES OF NEPHROPATHY DEVELOPMENT IN INDIVIDUALS WITH OVERWEIGHT AND OBESITY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Overweight and obesity are considered important risk factors for the development of renal damage. Increased body weight contributes to insulin resistance, arterial hypertension, dyslipidemia, chronic inflammation, and glomerular hyperfiltration. As a result, microalbuminuria, decreased filtration capacity, and signs of nephropathy develop in the kidneys. Therefore, early laboratory assessment of renal function in individuals with overweight and obesity has significant scientific and practical importance.